Model-Based Stator Fault Detection in Induction Motors - Kallesoe, C.S. (2008 IEEE Industry Applications Society Annual Meeting, 2008)
This paper addresses the subject of fault detection in the electrical parts of induction motors. In particular inter-turn short circuit faults are considered. The detection scheme is based on a motor-model, derived in the paper, which does not include the motor speed. This makes the detection scheme robust to any speed and torque changes on the motor shaft. The efficiency of the proposed detection scheme is demonstrated by simulations and by tests performed on a test setup with a customized designed induction motor.